KARAKTERISTIK FISIKOKIMIA SOBICOS FLAKES SEBAGAI MAKANAN BERINDEKS GLIKEMIK RENDAH (Physicochemical Characteristics of Sobicos Flakes as Suplement low glycemic index) - Ade Putri Sihotang; Terip Karo-Karo; Zulkifli Lubis (Universitas Sumatera Utara, 2019)
The aim of this research was to determine the effect of bran, sorghum flour, and wheat flour on nutritional content of flakes and the value of glycemic index of flakes as food low glycemic index. The formulation of bran, sorghum flour, wheat flour i.e. 25% : 55% : 20%, 30% : 50% : 20%, 35% : 45% : 20%, 40% : 40% : 20%, 45% : 35% : 20%, 50% : 30% : 20%, dan 55% : 25% : 20%, in this research has been found an analysis of physics characteristic i.e. color index and texture test, chemical characteristic i.e. carbohydrate content and crude fiber content. The formulation of bran, sorghum flour, wheat flour in flakes which had best quality and the best response of consumer was the flakes with ratio of 45% bran, 35% sorghum flour, and 20% wheat flour, the result of the glycemic index value of the best flakes was 54,9205 mg/dl which was classified as a low glycemic index. Key words : Bran, Flakes, Glycemic Index, Sorghum Flour ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh perbandingan bekatul, tepung sorgum, dan tepung terigu terhadap kandungan gizi flakes dan nilai indeks glikemik flakes sebagai makanan berindeks glikemik rendah. Perbandingan bekatul, tepung sorgum, dan tepung terigu yaitu 25% : 55% : 20%, 30% : 50% : 20%, 35% : 45% : 20%, 40% : 40% : 20%, 45% : 35% : 20%, 50% : 30% : 20%, dan 55% : 25% : 20%, pada penelitian ini telah dilakukan analisis terhadap karakteristik fisik yaitu indeks warna dan uji tekstur serta karakteristik kimia yaitu kadar karbohidrat dan kadar serat kasar. Formulasi perbandingan bekatul, tepung sorgum, dan tepung terigu dalam flakes dengan mutu dan penerimaan konsumen yang terbaik adalah flakes dengan perbandingan 45% bekatul, 35% tepung sorgum, dan 20% tepung terigu, menghasilkan nilai indeks glikemik flakes perlakuan terbaik sebesar 54,9205 mg/dl yang tergolong pada indeks glikemik rendah. Kata kunci : Bekatul, Flakes, Indeks Glikemik, Tepung Sorgum